A weak maximum principle for optimal control problems with mixed constraints under a constant rank condition - Andreani, Roberto; de Oliveira, Valeriano Antunes [UNESP]; Pereira, Jamielli Tomaz; Silva, Geraldo Nunes [UNESP] (Oxford University Press (OUP), 2020)
Necessary optimality conditions for optimal control problems with mixed state-control equality constraints are obtained. The necessary conditions are given in the form of a weak maximum principle and are obtained under (i) a new regularity condition for problems with mixed linear equality constraints and (ii) a constant rank type condition for the general non-linear case. Some instances of problems with equality and inequality constraints are also covered. Illustrative examples are presented.
Keywords: Constant rank; Mixed constraints; Weak maximum principle